Pengaruh Kecerdasan Linguistik dan Logis Matematis terhadap Hasil Belajar Matematika Siswa - Nurhidayati, Laela; Sridana, Nyoman; Novitasari, Dwi; Sripatmi, Sripatmi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the effect of linguistic intelligence and mathematical logic on the learning outcomes of mathematics students in grade VIII SMPN 2 Kediri academic year 2024/2025. This study is a quantitative study with the type of ex-post facto research, a population of 118 people with a sample of 92 students selected by simple random sampling technique. Data analysis techniques using descriptive analysis and simple linear regression analysis. Based on the data analysis obtained (1) 35 students (38%) have very high linguistic and mathematical logical intelligence, (2) 38 students (41%) have high mathematical learning outcomes, (3) students with very high linguistic and mathematical logical intelligence values 35 people, 2 of whom have very high mathematical learning outcomes, 22 people of high category and 11 people of medium to very low category. Based on the results of a simple linear regression analysis obtained regression equation that is Y=31.528+0.332 X, means there is an influence of linguistic intelligence and mathematical logic on the learning outcomes of mathematics students grade VIII SMPN 2 Kediri academic year 2024/2025 with a contribution of influence given by 19.3%.